Engineering orthogonal dual transcription factors for multi-input synthetic promoters - Andreas K. Brödel (Nature Portfolio, 2016)
Genetic circuits usually employ the same set of transcription factors which can act via repression or activation of the target promoter. Here the authors present dual activator-repressor switches, designed via directed evolution, for orthogonal logic gates and multi-input circuit architectures.